2021
DOI: 10.1186/s12870-021-03155-7
|View full text |Cite
|
Sign up to set email alerts
|

GWAS provides biological insights into mechanisms of the parasitic plant (Striga) resistance in sorghum

Abstract: Background Sorghum yields in sub-Saharan Africa (SSA) are greatly reduced by parasitic plants of the genus Striga (witchweed). Vast global sorghum genetic diversity collections, as well as the availability of modern sequencing technologies, can be potentially harnessed to effectively manage the parasite. Results We used laboratory assays – rhizotrons to screen a global sorghum diversity panel to identify new sources of resistance to Striga; determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Distinct genetic structuring of the sorghum panel was characterized using various criteria -BIC, NJ, as well and HBC. All these methods supported earlier work that showed clear population structures in sorghum (Kavuluko et al 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Distinct genetic structuring of the sorghum panel was characterized using various criteria -BIC, NJ, as well and HBC. All these methods supported earlier work that showed clear population structures in sorghum (Kavuluko et al 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Striga plant heads containing mature seeds collected from Alupe Kenya (0.45°, 34.13°) in 2018 were rstly threshed and sieved as described in (Kavuluko et al 2021). Afterwards, 25 mg of Striga seeds were surface sterilized by washing with 25 ml of 10 % (v/v) commercial sodium hypochlorite for 10 minutes with vigorous agitation.…”
Section: Striga Germination Assaysmentioning
confidence: 99%
“…For instance, using a natural population comprising 713 upland cotton accessions, Sun et al (2018) discovered a total of 10 and 15 SNPs that were significantly associated with relative survival rate and salt tolerance level, respectively, among which two SNPs (i46598Gh and i47388Gh) on genomic region D09 were simultaneously linked with the two traits. A GWAS using a diverse panel of 206 genotypes identified genetic loci associated with Striga ( Striga hermonthica ) resistance genes in sorghum ( Kavuluko et al, 2021 ). The study detected secondary cell wall modification genes for lignin biosynthesis genes, including PMT2 Methyltransferase at position S2_59157949, secondary wall NAC TF 4 at S6_60968111 and early nodulin 93 at S10_2576197.…”
Section: Genomics and Pan-genomicsmentioning
confidence: 99%
“…Additionally, they identified the Fasciclin-like arabinogalactan protein 11 that regulates plasticity and integrity of cell walls at position S9_5732771, as well as revealing the association of Striga resistance with the Ethylene-responsive transcription factor ERF113 at S4_50512606. ERF113 is a key regulator of both jasmonic acid (JA) and salicylic acid (SA) mediated defense pathways in plants ( Kavuluko et al, 2021 ). GWAS to understand the genetic architecture of grain yield (GY) and flowering time under drought and heat stresses in a collection of 300 tropical and subtropical maize inbred lines using 381 165 genotyping-by-sequencing (GBS) SNPs revealed that 1549 SNPs were significantly associated with all the 12 trait-environment combinations, with 193, 95, and 405 candidate genes associated with GY, anthesis-silking interval (ASI), and anthesis date (AD), respectively ( Yuan et al, 2019 ).…”
Section: Genomics and Pan-genomicsmentioning
confidence: 99%
“…Water, nutrients, and other molecules including mRNA (Kim et al, 2014), small RNA (Shahid et al, 2018), DNA (Yang et al, 2019), and proteins (Liu et al, 2020;Shen et al, 2020) are directly transferred through haustorial connection. In addition to natural variation in low germination stimulation (Dayou et al, 2021;Mallu et al, 2021), post-germination host resistance in Striga hermonthica is often apparent across diverse hosts, for example due to induction of an intense hypersensitive response, formation of a mechanical barrier, or failure of the parasite to form vascular connections (Mbuvi et al, 2017;Mutinda et al, 2018;Kavuluko et al, 2020). Much of this genetic variation in natural resistance may result from host populations' local adaptation to parasitism across the range of Striga hermonthica (Bellis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%